Local and timely antimicrobial resistance data for local and national actions: the early implementation of an automated tool for data analysis at local hospital level in Thailand - Srisuphan, V; Klaytong, P; Rangsiwutisak, C; Tuamsuwan, K; Boonyarit, P; Limmathurotsakul, D (Oxford University Press, 2023)
Background In low- and middle-income countries (LMICs), hospitals can rarely utilize their own antimicrobial resistance (AMR) data in a timely manner. Objectives To evaluate the utility of local AMR data generated by an automated tool in the real-world setting. Methods From 16 December 2022 to 10 January 2023, on behalf of the Health Administration Division, Ministry of Public Health (MoPH) Thailand, we trained 26 public tertiary-care and secondary-care hospitals to utilize the AutoMated tool for Antimicrobial resistance Surveillance System (AMASS) with their own microbiology and hospital admission data files via two online meetings, one face-to-face meeting and online support. All meetings were recorded on video, and feedback was analysed. Results Twenty-five hospitals successfully generated and shared the AMR reports with the MoPH by 28 February 2023. In 2022, the median frequency of hospital-origin bloodstream infections (BSIs) caused by carbapenem-resistant Escherichia coli (CREC) was 129 (range 0–1204), by carbapenem-resistant Klebsiella pneumoniae (CRKP) was 1306 (range 0–5432) and by carbapenem-resistant Acinetobacter baumannii (CRAB) was 4472 (range 1460–11 968) per 100 000 patients tested for hospital-origin BSI. The median number of all-cause in-hospital deaths with hospital-origin AMR BSI caused by CREC was 1 (range 0–18), by CRKP was 10 (range 0–77) and by CRAB was 56 (range 7–148). Participating hospitals found that the data obtained could be used to support their antimicrobial stewardship and infection prevention control programmes. Conclusions Local and timely AMR data are crucial for local and national actions. MoPH Thailand is inviting all 127 public tertiary-care and secondary-care hospitals to utilize the AMASS. Using any appropriate analytical software or tools, all hospitals in LMICs that have electronic data records should analyse and utilize their data for immediate actions.